A Neutral, Chiral, Bis(imidazolidine)‐Derived NCN‐Type Palladium Pincer Complex with Catalytic Activity. Issue 5 (4th January 2013) - Arai, Takayoshi; Oka, Ikiyo; Morihata, Takuma; Awata, Atsuko; Masu, Hyuma
<x xml:space="preserve">Abstract</x> Caught in a pincer: A chiral, imidazolidine‐derived NCN‐type palladium pincer complex has been prepared using a ligand introduction technique. Single‐crystal X‐ray diffraction analysis of this complex showed a well‐organized asymmetric sphere. The neutral palladium/chloride version exhibited significant catalytic activity for the reaction of nitroalkenes with malononitrile to give products in a highly enantioselective manner (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>